2010
DOI: 10.1074/jbc.m109.034579
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor-κB (NF-κB) Is a Novel Positive Transcriptional Regulator of the Oncogenic Wip1 Phosphatase

Abstract: The nuclear factor-B (NF-B) family of transcription factors plays a key role in inflammation and augments the initiation, promotion, and progression of cancer.NF-B activation generally leads to transcriptional enhancement of genes important in cell survival and cell growth, which is exploited in cancer cells. In this study, we identify an additional oncogene, PPM1D, which encodes for Wip1, as a transcriptional target of NF-B in breast cancer cells. Inhibition of NF-B or activation of NF-B resulted in decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 51 publications
4
40
0
Order By: Relevance
“…38,44 The strategy specifically directed to the transient activation of Wip1 in patients loop downregulating NFκB function following exposure to an inflammatory stress. 42,43 To test whether negative regulation of NFκB function by overexpressed Wip1 contributed to the increased sensitivity to cisplatin, we determined the levels of p65 S536 phosphorylation in our system. As shown in Figure 3A, we observed that in tumor cells with elevated levels of Wip1, the levels of activating S536 phosphorylation of p65 were lower both before and after cisplatin treatment compared with control cells, while the levels of total p65 protein remained constant.…”
Section: Resultsmentioning
confidence: 99%
“…38,44 The strategy specifically directed to the transient activation of Wip1 in patients loop downregulating NFκB function following exposure to an inflammatory stress. 42,43 To test whether negative regulation of NFκB function by overexpressed Wip1 contributed to the increased sensitivity to cisplatin, we determined the levels of p65 S536 phosphorylation in our system. As shown in Figure 3A, we observed that in tumor cells with elevated levels of Wip1, the levels of activating S536 phosphorylation of p65 were lower both before and after cisplatin treatment compared with control cells, while the levels of total p65 protein remained constant.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, PPM1D has been shown to be involved in a series of interactions that could account for non-P53-related functions, including the regulation of progesterone receptor expression, specific DNA repair mechanisms and control of the NF-kB pathway. 24 In fact, our previous studies have shown that PPM1D silencing and inhibition of its phosphatase activity are selectively lethal for breast and ovarian clear cell cancer cell lines in a manner that does not completely correlate with TP53 gene status. 8,9 In agreement with our previous observations, we show here that PPM1D overexpression is more prevalent than gene amplification.…”
Section: Discussionmentioning
confidence: 99%
“…24 In previous studies, we have shown that PPM1D expression and phosphatase activity are required for the survival of cancer cells derived from breast 9,25 and ovarian clear cell carcinomas 8 harbouring amplification of 17q23.2. Our previous results provide direct evidence that PPM1D may be one of the drivers of this amplicon [8][9][10] and that PPM1D may constitute a therapeutic target for a subgroup of breast and ovarian cancers harbouring PPM1D gene amplification.…”
mentioning
confidence: 99%
“…Human Cyclin D1 (positive control, see Nakuci et al, 2006), p53 and PPM1D promoter regions were cloned upstream of the luciferase gene in the pGL3-Basic vector to produce pGL3-hCycD1 (a 2.5 kb gene core promoter), -hp53 (a 140 bp (À128-þ 12) gene core promoter) and -hPPM1D (a 849 bp gene core promoter) plasmids (see Materials and methods). According to (Wang and ElDeiry, 2006) p53 activates its own promoter, and (Lowe et al, 2010) nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB) activates the PPM1D promoter. In co-transfection experiments pcDNA3-p53 and pcDNA3-NF-kB/p65 triggered a 415-fold increase in pGL3-hp53 and pGL3-hPPM1D activity, respectively (Figure 1g).…”
Section: Brca1-iris Triggers Wip1 Expression In a P53-dependent And -mentioning
confidence: 99%